Analisis Potensi dan Kontribusi Pajak Hotel Terhadap Pendapatan Asli Daerah Pemerintah Kota Padang (Studi Kasus di Dinas Pengelolaan Keuangan Kota Padang) - Ardiles Ardiles; Erly Mulyani (Universitas Negeri Padang, 2014)
The purpose of this study was for determining how the potential and contribution of the Hotel Tax Revenue for the Revenue receipts of Padang, and the influence of the potential and contribution to the Hotel Tax Revenue receipts of Padang. The research used descriptive method quantitative and quanlitative, the research sources by collecting data, presenting and explaining the data through the numbers. This result indicate that the Hotel Tax has huge potential and continues to increased from 2008 – 2014. This is evidenced by calculating the difference between realization and potential of the Hotel Tax revenues in 2008 is 31,28%, in 2009 is 47,13%, in 2010 is about 39.13%, in 2011 is 53,04 %, in 2012 is 52,82 %, in 2013 is 53,27 % and in 2014 is 52,24 %. This result showed the conclusion that the potential tax revenue Hotel in Padang did not reflect its true potential, therefore the Department of Revenue need to optimizing Hotel Tax receipts of Padang for local revenue to be increased. Keywords : Potential tax hotel, hotel tax retribution, original regional revenue